2013
DOI: 10.3141/2368-08
|View full text |Cite
|
Sign up to set email alerts
|

Development of Full-Scale Reflective Cracking Test at the FAA National Airport Pavement Test Facility

Abstract: Asphalt concrete overlays must be designed and constructed to withstand reflective cracking. However, the current FAA overlay design procedure (Advisory Circular 150/5320-6E) does not address this common form of premature failure. This paper presents a research project that studied one of the accepted causes of reflection cracks: horizontal movements concentrated at joints in the existing portland cement concrete pavement. A prototype, the temperature-effect simulation system, was developed at the FAA National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Details of the pavement structures are presented in Table 1 with the material properties of each layer. The pavement structure mimics the pavement section used for full-scale testing of thermally-induced reflective cracks conducted by the Federal Aviation Administration (FAA) ( 5 ). The pavement layer thickness and material properties are shown in Table 1.…”
Section: Pavement Model Details and Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the pavement structures are presented in Table 1 with the material properties of each layer. The pavement structure mimics the pavement section used for full-scale testing of thermally-induced reflective cracks conducted by the Federal Aviation Administration (FAA) ( 5 ). The pavement layer thickness and material properties are shown in Table 1.…”
Section: Pavement Model Details and Materials Propertiesmentioning
confidence: 99%
“…Horizontal displacement was utilized to simulate thermally-induced joint opening of PCC. However, the developed system only considered the thermal contraction and expansion of PCC, the slab curling effect was not considered in the study ( 5 ). Based on full-scale testing, it was found that the inclusion of one-inch interlayer could extend overlay life by 15%.…”
mentioning
confidence: 99%